A new species of Sinocyclocheilus (Cypriniformes, Cyprinidae) from the Beipan-Jiang in Guizhou, China - Leishan Wang; Qi Luo; Renyi Zhang (ZooKeys)
Sinocyclocheilus zhenningensis sp. nov. from the Dabang-He of the Beipan-Jiang Basin in Zhenning County, Guizhou Province, China, is described based on morphological and molecular evidence. The new species can be distinguished morphologically from all congeners in this genus by: (1) normal eyes (5.8%–8.2% SL), presence of pigmentation, with a humpback and no horn structure; (2) pelvic fin rays ii-8, dorsal-fin rays iii-8, stiff and stout last unbranched ray; (3) body depth normal (26.5%–30.1% SL) and covered with irregular black spots, body scaled, but scales buried beneath the skin; (4) lateral line complete, slightly curved ventrally, 42–47 lateral line pored scales; and (5) pectoral fin short, not reaching the anterior base of pelvic fin. Based on the mitochondrial cytochrome b (Cytb) gene phylogenetic tree, S. zhenningensis sp. nov. is strongly supported as sister to the S. cyphotergous-S. multipunctatus subclade. The minimum genetic distance between Sinocyclocheilus zhenningensis sp. nov. and its congeneric species is 3.8%.